Inflammation is a critical factor for successful regeneration of the adult zebrafish retina in response to diffuse light lesion - Bludau, Oliver; Weber, Anke; Bosak, Viktoria; Kuscha, Veronika; Dietrich, Kristin; Hans, Stefan; Brand, Michael (Frontiers in Cell and Developmental Biology, 2024)
Inflammation can lead to persistent and irreversible loss of retinal neurons and photoreceptors in mammalian vertebrates. In contrast, in the adult zebrafish brain, acute neural inflammation is both necessary and sufficient to stimulate regeneration of neurons. Here, we report on the critical, positive role of the immune system to support retina regeneration in adult zebrafish. After sterile ablation of photoreceptors by phototoxicity, we find rapid response of immune cells, especially monocytes/microglia and neutrophils, which returns to homeostatic levels within 14 days post lesion. Pharmacological or genetic impairment of the immune system results in a reduced Müller glia stem cell response, seen as decreased reactive proliferation, and a strikingly reduced number of regenerated cells from them, including photoreceptors. Conversely, injection of the immune stimulators flagellin, zymosan, or M-CSF into the vitreous of the eye, in spite of the absence of a retinal lesion, leads to a robust proliferation response and the up-regulation of regeneration-associated marker genes in Müller glia. Our results suggest that neuroinflammation is a necessary and sufficient driver for retinal regeneration in the adult zebrafish retina.